The Influence of Socialization on Talent Interests and Extracurricular in Schools - Hafifah Madaniah; Rina Maryanti (Indonesian Journal of Multidiciplinary Research, 2023)
This study aims to determine the influence of socialization on interests and talents as well as the existence of extracurricular in schools on the level of insight of students of State Junior High School 12 Bandung, Indonesia. The sample in this study was 50 students of State Junior High School 12 Bandung. The instrument in this study used a questionnaire through Google form on students of The State Junior High School 12 Bandung. The results showed an increase between the average value of the pre-test and post-test, starting with a value of 61.25 to 70. The results showed an average N-Gain score of 20.63% (N-Gain 40%), meaning that socialization about interests and talents as well as extracurricular in schools towards student insights was not effectively used in students of State Junior High School 12 Bandung. In this study, a t-test was carried out known T count (-5.28119) T table (2.26216). Thus, students' post-test scores increased insignificantly. The impact of this research is that students are expected to be insightful about their talent interests.